Facile synthesis of MgO–Mg2SiO4 composite ceramics with high strength and low thermal conductivity. Issue 14 (15th July 2021) - Ren, Xinming; Ma, Beiyue; Fu, Gaofeng; Qian, Fan; Liu, Guoqi; Yu, Jingkun; Li, Yawei
Abstract: The recycling of solid waste is a win-win solution for humans and nature. For this purpose, magnesite tailings and silicon kerf waste were employed to prepare MgO–Mg2 SiO4 composite ceramics by solid-state reaction synthesis in the present work. Then, effects of sintering temperature and raw material ratio on as-prepared ceramics were systematically studied. As-prepared ceramics showed improvement in their relative density (from 47.55%–68.12% to 90.96%–95.25%) and cold compressive strength (from 7.34–118.66 MPa to 303.39–546.65 MPa) with the increase in sintering temperature from 1300 to 1600 °C. In addition, it was found that Si promoted synthesis process of Mg2 SiO4 phase through transient liquid phase sintering and Fe2 O3 accelerated sintering process through activation sintering. Consequently, the presence of Mg2 SiO4 phase effectively improved the density and strength of MgO–Mg2 SiO4 composite ceramic, while reducing its thermal conductivity. This work provides a potential reutilization strategy for magnesite tailings, and as-prepared products are expected to be applied in fields of construction, metallurgy, and chemical industry.